Evaluation of a 'drop box' doorstep assessment service to aid remote assessments for COVID-19 in general practice. Issue 1 (29th March 2021) - Irving, Greg; Lawson, David; Tinsley, Adele; Parr, Helen; Whittaker, Cheryl; Jones, Hayley; Cox, Stephen
Abstract : COVID-19 is an established threat whose clinical features and epidemiology continues to evolve. In an effort to contain the disease, the National Health Service has adopted a digital first approach in UK general practice resulting in a significant shift away from face-to-face consultations. Consequently, more consultations are being completed without obtaining objective recording of vital signs and face-to-face examination. Some regions have formed hot hubs to facilitate the review of suspected COVID-19 cases and keep their practice site 'clean' including the use of doorstep observations in avoiding the risk of face-to-face examination. To support the safe, effective and efficient remote assessment of suspected and confirmed patients with COVID-19, we established a doorstep assessment service to compliment telephone and video consultations. This allows physiological parameters such as temperature, pulse, blood pressure and oxygen saturation to be obtained to guide further triage. Quality improvement methods were used to integrate and optimise the doorstep assessment and measure the improvements made. The introduction of a doorstep assessment service increased the proportion of assessments for patients with suspected COVID-19 in routine care over weeks. At the same time we were able to dramatically reduce face-to-face assessment over a 6-week period by optimising through a range of measures including the introduction of a digital stethoscope. The majority of patients were managed by their own general practitioner following assessment supporting continuity of care. There were no adverse events during the period of observation; no staff absences related to COVID-19. Quality improvement methods have facilitated the successful integration of doorstep assessments into clinical care.